Investment License and Environmental Sustainability In Perspective of Law Number 11 the Year 2020 Concerning Job Creation - Rahmat Saputra; Rama Dhianty (Administrative and Environmental Law Review, 2022)
Many factors influence and even hinder investment activities in Indonesia, including reforming policies and their implementation, bureaucratic problems and obstacles, uncertainty in the interpretation and implementation of regional autonomy, human resources, and labor policy issues, and the high level of corruption. The government made a breakthrough in the regulation of investment licensing through law no. 11 of 2020 concerning job creation with the omnibuslaw method. In addition to investment issues, changes to regulations in the environmental sector that revise, delete and revoke several articles contained in the provisions of Law no. 32 of 2009 concerning PPLH. The purpose of this article is to find out the investment licensing arrangements in the enactment of law no. 11 of 2020 concerning job creation and knowing environmental sustainability after the enactment of law no. 11 of 2020 concerning work creation. This research method is a type of normative legal research with a legal approach, historical approach, and conceptual approach. Research results with the enactment of law no. 11 of 2020 concerning job creation, more or less regulatory arrangements will affect investment in a country. Investment regulations that do not overlap and do not conflict with each other are the expectations of investors. For this reason, it is necessary to arrange regulations that have the spirit to encourage and support investment growth and the sustainability assessment criteria in law no. 11 of 2020 concerning job creation and its derivatives are still following environmental prevention instruments which include the process of planning, utilization, control, maintenance, supervision, and law enforcement, it's just that community involvement in the Amdal document is indeed reduced as in the provisions of the work creation law which amends Article 26 UU no. 32 of 2009 regarding the preparation of the amdal document, it is carried out by not involving the community who are directly affected by the planned business and/or activity.